2019
DOI: 10.1177/1533033819858363
|View full text |Cite
|
Sign up to set email alerts
|

A Transfer Learning Approach for Malignant Prostate Lesion Detection on Multiparametric MRI

Abstract: Purpose: In prostate focal therapy, it is important to accurately localize malignant lesions in order to increase biological effect of the tumor region while achieving a reduction in dose to noncancerous tissue. In this work, we proposed a transfer learning–based deep learning approach, for classification of prostate lesions in multiparametric magnetic resonance imaging images. Methods: Magnetic resonance imaging images were preprocessed to remove bias artifact and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 49 publications
(65 reference statements)
0
36
0
Order By: Relevance
“…The flow diagram is depicted in Figure 1 . In total, 27 articles were eligible for inclusion in this review [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. From these, 13 studies reported enough information to perform a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow diagram is depicted in Figure 1 . In total, 27 articles were eligible for inclusion in this review [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. From these, 13 studies reported enough information to perform a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the details regarding the selected populations were heterogenous between studies. Some papers limited their description to the number of positive and negative samples [27,31], while others mentioned the PCa lesion distribution per GS [11,23] and/or the volume distribution [16,21]. Both characteristics describe the type of population used and whether the PCa lesions are clinically relevant [2].…”
Section: Discussionmentioning
confidence: 99%
“…The SVM method used discriminative features in training that resulted in an AUC score of 0.89 [95]. All of the studies listed in Table 4 used radiologists to determine their ground truth [77,[92][93][94][95][97][98][99][100]. These studies highlight the ability of DL algorithms to predict the likelihood of a lesion's malignancy based upon Gleason scores.…”
Section: Prostate Lesion: Characterizationmentioning
confidence: 99%
“…These features can then be used to develop predictive models using machine learning methods when "ground-truth" voxel-level data is available. Many investigators have explored and yielded promising results from using radiomics and machine learning of mpMRI for PCa detection [64][65][66][67][68], tumour aggressiveness (Gleason score) classification, and staging [62,[69][70][71][72][73][74]. Voxel-level tumour biology distributions generated by predictive models using mpMRI can then be used to drive biological optimisation of prostate radiotherapy as demonstrated by the bottom row of Figure 1.…”
Section: Biological Optimisation Of Prostate Imrt Using Patient-specimentioning
confidence: 99%